Policy, Knowledge and Promoting a Democratic Stance - Wahlström, Ninni (Equity, Teaching Practice and the Curriculum, 2022)
In this chapter, the purpose is to explore the boundaries of three different concepts of knowledge and how different elements of a transnational education framework, Education 2030, become adaptable, or unadaptable, to a certain knowledge concept. The Organisation for Economic Co-operation and Development (OECD) has identified environmental, economic and social challenges to handle within education. Moreover, the OECD has claimed that an overarching purpose for meeting these challenges can be summarised with the term well-being. Education for well-being is said to prepare people not only for work but also to become active, responsible and engaged citizens. The historical traditions and characters of three different concepts of knowledge with relevance for curricula and teaching are presented together with an analysis of the OECD policy framework in relation to the different knowledge concepts. The knowledge concepts are social realism, transactional realism (pragmatism) and Bildung. While Bildung means offering the world to the students by focusing on content with which the learner can engage, transactional realism presents the world as incomplete and unresolved, focusing on inquiry, reflective thinking and interactive communication. Social realism, however - starting off from a division between mind and object, theory and practice - describes the world to the students by focusing on scientific knowledge. In recent years, the mission for schools to provide good conditions for students to acquire knowledge has been emphasised in international and national educational policies - not least based on international knowledge measurements such as Programme for International Student Assessment and comparisons of results. This chapter explores the boundaries of three different concepts of knowledge and how different elements of a transnational education framework, Education 2030, become adaptable, or unadaptable, to a certain knowledge concept. It introduces the Organisation for Economic Co-operation and Development framework of Education 2030. The chapter then discusses the character of the policy framework and the educational implications of connections and boundaries between the different knowledge concepts. Social realism is based on the assumptions that the main role of school is to constitute a place for knowledge transmission, that some knowledge is more worthwhile than other knowledge and that differences between different forms of knowledge must constitute the basis for curricula.